Expandindo a área de cobertura de um sistema multi-robôs através de redes multicamadas e um middleware de base de dados em tempo real - Caetano, Leandro José (2015)
The communication between robots is essential and of great interest in the robotics research eld. It is from it that the robots can discover and pass on information about obstacles in their way, pass on to the other robots information about a target that other robot can not detect, determine together which is the best route to follow, among others, until the goals are achieved. The major di culty in the context where robot communication exists in an Ad Hoc network is distancing the robots from each other. So that one of them for example, may migrate to another area leaving their initial formation, completing a speci c task and return to the starting point, in addition to distancing the whole formation of robots from a central computer. By distancing a robot from the limits imposed by other means will entail a loss of signal compromising communication between them. This way, knowing a wireless network coverage area where robots will be connected is an important process for the implementation of a system of communication between robots. The aim of this work is to demonstrate the feasibility of expanding the coverage area of a wireless network, to be used in multi-robot systems, of a formation of robots that use a Real Time Database (RTDB) in multilayer networks that using the IEEE 802.11 and 802.15.4, analyzing the behavior of this expansion in relation to connectivity of robots, coverage area and interference in wireless networks. According to the performed experiments, the results demonstrate the robustness and reliability of the proposed scenario and it was shown that the use of multilayer networks provides a greater range in the coverage area of a robot training.